The anatomy of the fruit in relation to the propensity of citrus species to split - García-Luis, Amparo (2012)
The anatomy of the fruit has been compared in three prone-to-split mandarin hybrids (Nova, Ellendale and Murcott), several cultivars of clementine mandarin (Fino, Clementina de Nules and Orogrande), and in Owari satsuma mandarin. The fruit of the hybrids is oblate to subglobose and usually presents an open stylar end disrupted by a navel formed by the ﬂoral meristem, which is conserved near the apex of the fruit. In the non-prone-to-split clementines as well as in Owari satsuma, the ﬂoral axis protrudes inside the style, and the ﬂower meristem is lost through abscission shortly after petal fall. The abaxial side of the carpels fuses with the ﬂower axis forming at the stylar end of the fruit a solid tissue which externally has a small scar at the place of style abscission. Most of the fruits in these cultivars have no navel. In addition, the fruit of clementine is slightly oblate or globose. The relevance of these anatomical characteristics as regards to splitting is supported by the differences between the split and non-split fruits in Nova, the split fruit being more oblate in shape and having a bigger navel than non-split fruit. However, the effect of applied growth regulators on fruit splitting could not be correlated with their effect on the anatomy of the fruit. Additional factors not contemplated in the study also inﬂuence fruit splitting.